Przedmiot lobbingu z perspektywy etycznej - Kalinowski, Marcin (Annales. Etyka w Życiu Gospodarczym, 2013)
The aim of the article is a review of the wide spectrum of lobbying formulations and definitions to answer questions regarding the areas of lobbying activity. The author argues that lobbying is a wide scope of activities that lobbyists undertake according to their expectations and preferences. Ethical reflections on lobbying activity should then take into consideration the conditions in which the main players on the democratic political scene interact with each other.